Study of Fish Types at Parit 1 Kuala Tungkal Market for High School-Biology Popular Scientific Book - DINI MAIDIKA; JODION SIBURIAN; AFRENI HAMIDAH (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2016)
Kuala Tungkal is a district located in the east coast Province of Jambi. Kuala Tungkal has excellent potential in the field of fisheries. Various types of fish sold in the Parit 1 Kuala Tungkal Market. Fish is a among the examples of the diversity of fauna in Indonesia. This diversity needs to be introduced to students to improve the contextuality of learning. This study aims to determine the type of fishes being sold in the market. Student and teacher perceptions about the book that developed based on the results of fish studies in the Parit 1 Market. This research is descriptive and analytic. The study describes the type of fishes being sold in the Parit 1 Kuala Tungkal Market through direct observation and interviews with fish traders, as well as the perceptions of students and teachers of high school of Kuala Tungkal (SMA N 1 Kuala Tungkal) about the book. The results showed there are 23 species of saltwater fish from 15 families and 7 species of freshwater fish from 6 families. Students appraised the book belongs as “very good” with a value of 94% and teachers also appraised the book as “very good” with a value 86,7%.